2019
DOI: 10.1088/1361-6587/ab31a4
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism for increasing density peaking in tokamaks: improvement of the inward particle pinch with edge E × B shearing

Abstract: Developing successful tokamak operation scenarios, as well as confident extrapolation of presentday knowledge requires a rigorous understanding of plasma turbulence, which largely determines the quality of the confinement. In particular, accurate particle transport predictions are essential due to the strong dependence of fusion power or bootstrap current on the particle density details. Here, gyrokinetic turbulence simulations are performed with physics inputs taken from a JET power scan, for which a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…In particular, we notice a significant peaking of the density profile primarily located in the outer regions, thus improving the agreement of the GENE-Tango density profile with the experimental measurements and TGLF-ASTRA. These findings are in agreement with the flux-tube results of reference [85] suggesting that the E × B shear might enhance inward particle pinch.…”
Section: Electrostatic Gene-tango Simulation With Collisions and Exte...supporting
confidence: 92%
“…In particular, we notice a significant peaking of the density profile primarily located in the outer regions, thus improving the agreement of the GENE-Tango density profile with the experimental measurements and TGLF-ASTRA. These findings are in agreement with the flux-tube results of reference [85] suggesting that the E × B shear might enhance inward particle pinch.…”
Section: Electrostatic Gene-tango Simulation With Collisions and Exte...supporting
confidence: 92%
“…look into the normalized electron particle flux (corresponding to the values of the last column of the table), observing that only the presence of the E × B shearing non-negligibly changes it, leading to slightly smaller values of T e Γ e /(q e + q i ). This could cause a tiny increase in the density peaking due to E × B shearing for the NBI case as also reported in [29], but as the rotation is relatively small with respect to typical JET Hmode plasmas with only 8 MW of NBI heating (central v tor = 110 km s −1 ), the influence of E × B shearing on the peaking is expected to be small. However, looking into the absolute values of heat fluxes, it is evident that while the E × B shearing only slightly affects T e Γ e /(q e + q i ), its presence reduces the single fluxes by ∼50%.…”
Section: Gyrokinetic and Integrated Transport Modelling Of The Icrh A...mentioning
confidence: 56%
“…However, at the lowest collisionality, as might have been expected from the formation of the internal transport barrier, the radial electric field has developed a substantial well, see blue curve on figure 15. Previous experimental observations, closer to the top of the pedestal have indicated that the changes to the radial electric field can have an important impact on particle transport [11][12][13]. This is another indication that the observed changes at the lowest collisionality are beyond a direct effect of the collisionality on the ITG and TEM contributions to the particle flux.…”
Section: Role Of the Radial Electric Fieldmentioning
confidence: 81%
“…The E × B shearing rate is known to be a regulator for turbulence and turbulent transport in plasmas [10]. It has been shown that a sufficiently strong E × B shearing rate can have a significant effect upon particle transport specifically [11][12][13]. It is impossible from the multi-machine database to isolate this effect.…”
Section: Introductionmentioning
confidence: 99%